Respeito às normas e crescimento econômico: Como promotores públicos garantem o cumprimento das leis e promovem o crescimento econômico no Brasil - Salo Vinocur Coslovsky (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– This paper examines how Brazilian prosecutors promote compliance with labor and environmental laws while preserving or even enhancing the competitiveness of local firms. In the cases analyzed, prosecutors realize that the bottlenecks that prevent compliance are often located outside the firm and its immediate value chain, so punishment or pedagogy, when used in isolation, are not likely yield meaningful results. Instead, they locate key bottlenecks, assess them, and then, depending on the task ahead, bring together a series of public, private, and non-profit institutions willing to share, according to their respective tolerance and ambition, the risks and benefits associated with the necessary change. This process, which prosecutors themselves call to stitch it together, effectively modifies the environment in which firms operate so as to make compliance the easy and obvious choice for all involved.
Keywords: K32; K42; L50; 330